2017
DOI: 10.1002/pola.28568
|View full text |Cite
|
Sign up to set email alerts
|

Photoactive Polymers with Benzocyclobutene/Silacyclobutane Dual Crosslinked Structure and Low Dielectric Constant

Abstract: Low dielectric photopatternable materials have aroused much interest owing to their potential application as alternatives of conventional photoresists. Although a number of photosensitive groups have been established to construct photopatternable materials for many years, it is still a challenge to introduce them into polymer chains via a facile and control polymerization technique, such as living free radical polymerization. In this work, on the basis of the photoactive silaycyclobutene moiety, a new monomer,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 34 publications
2
22
0
Order By: Relevance
“…Aer the addition of methylhexahydrophthalic anhydride (MeHHPA) as the curing agent and 2-methylimidazolate (2-MI) as the accelerator with a stoichiometric amount, the cured epoxy resins with low dielectric properties and improved thermal stabilities were obtained. Additionally, we prepared other three kinds of cured commercial epoxy resins in the same method and characterized their properties for comparison, including bisphenol A epoxy resin (BPA-EP), bisphenol F epoxy resin (BPF-EP) and 4 All other solvents were obtained commercially and used without further purication.…”
mentioning
confidence: 99%
“…Aer the addition of methylhexahydrophthalic anhydride (MeHHPA) as the curing agent and 2-methylimidazolate (2-MI) as the accelerator with a stoichiometric amount, the cured epoxy resins with low dielectric properties and improved thermal stabilities were obtained. Additionally, we prepared other three kinds of cured commercial epoxy resins in the same method and characterized their properties for comparison, including bisphenol A epoxy resin (BPA-EP), bisphenol F epoxy resin (BPF-EP) and 4 All other solvents were obtained commercially and used without further purication.…”
mentioning
confidence: 99%
“…So et al synthesized a copolymer of styrene and 4-VBCB through free radical polymerization and found that BCB dramatically increases the T g of polystyene after ring opening and crosslinking [23]. Huang et al synthesized a copolymer containing BCB and silacyclobutane side groups with low dielectric constants (approximately 2.30 MHz to 10 MHz) through atom transfer radical copolymerization [24]. The thermal crosslinking of BCB can also be applied in the preparation of nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
“…Benzocyclobutene containing polymers are of great interest in modern science because they have a variety of prominent characteristics, such as great thermal stability [1][2][3][4], low water uptake [1,5,6], high alkaline and acid stability [7,8], to complete with good dielectric properties [1,[9][10][11]. These features make such materials prospective to use as dielectric coatings and this, in turn, stimulates the searching of benzocyclobutene containing monomers and their precursors.…”
Section: Introductionmentioning
confidence: 99%